1993
DOI: 10.1172/jci116829
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide decreases canine cerebrospinal fluid production. In vivo evidence for NaCl cotransport in the central nervous system.

Abstract: Na/K/2CI cotransport carrier plays an important role in fluid absorption and secretion in many epithelial tissues. The role of the carrier, however, in mammalian choroidal cerebrospinal fluid (CSF) production has been controversial. We used ventriculo-cisternal perfusion (VCP) labeled with blue dextran with or without bumetanide and measured choroidal CSF production in anesthetized, and paralyzed, mechanically ventilated dogs. During 3 h of VCP, mean intracerebroventricular and arterial pressures, Paco2, pH, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 28 publications
4
55
0
Order By: Relevance
“…It would thus be interesting to investigate the long-term effects of ion transport changes on CSF dynamics. Inhibition of the three main transporters investigated in this study has previously been reported to inhibit CSF production (25)(26)(27)(37)(38). We have shown a decrease in expression of the Na ϩ -H ϩ exchanger and a probable increase in phosphorylation of the Na ϩ -K ϩ -ATPase ␣1-subunit.…”
Section: Figsupporting
confidence: 61%
“…It would thus be interesting to investigate the long-term effects of ion transport changes on CSF dynamics. Inhibition of the three main transporters investigated in this study has previously been reported to inhibit CSF production (25)(26)(27)(37)(38). We have shown a decrease in expression of the Na ϩ -H ϩ exchanger and a probable increase in phosphorylation of the Na ϩ -K ϩ -ATPase ␣1-subunit.…”
Section: Figsupporting
confidence: 61%
“…channels. In the pharmacology category, particularly useful have been diuretic agents that reduce CSF formation by slowing ion transport across CP (Davson and Segal, 1970;Javaheri and Wagner, 1993;McCarthy and Reed, 1974;Murphy and Johanson, 1990;Praetorius and Nielsen, 2006;Johanson, 1980, 1991). Clearly, the pharmacologic inhibitory linkage in the CP-CSF nexus is consistent with physiologic coupling of CP ion transport to CSF formation.…”
Section: Cerebrospinal Fluid Secretion By Cpmentioning
confidence: 99%
“…Bumetanide (an NKCC1 inhibitor) and furosemide (a KCC inhibitor), alone or in combination with acetazolamide, have been documented to decrease CSF production in canine and feline models. 65,70 The effect of bumetanide on CSF production, in conjunction with its selectivity for NKCC1, highlights the importance of this transporter in CSF homeostasis. Animal evidence also reveals the effect of furosemide in disrupting ion transport across the blood-CSF barrier, which reduces the rate of CSF secretion.…”
Section: Medical Management Of Hydrocephalus By Targeting Csf Productionmentioning
confidence: 99%